BIBLIOMETRIC STUDY ON THE UTILIZATION OF GARDENING AS A MODE TO IMPROVE PHYSICAL ACTIVITY FOR ELDERLY - Prasetyo, Iqbal; Djuwita, Ratna (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study utilized bibliometric analysis to map the literature on the utilizaiton of gardening as a mode to improve physical activity among older adults. The dataset was obtained from Scopus for the period 2004–2024 and analyzed using RStudio and VOSViewer. The results revealed that physical activity and gardening were dominant themes with strong connections to elderly, aging, and quality of life. Most studies originated from Western and East Asian countries, while Southeast Asia, including Indonesia, presents significant opportunities for further research in this field. Keywords such as horticultural therapy and human issues in horticulture remain underexplored, offering new research avenues. This study recommends the adaptation of gardening as a community-based health intervention and the application of scientific measurements such as METs using discovered keywords within Indonesia's cultural context.